Environmental sustainability of semiconductor supply chains - Pervushyna, Sofiia (2025)
The semiconductor industry is a critical driver of modern technology, yet it faces increasing scrutiny regarding its environmental impact. To inform stakeholders, many semiconductor companies release sustainability reports detailing their environmental efforts. However, the complexity and comparability of these reports vary significantly. This thesis conducts a comparative analysis of three key semiconductor manufacturers – Intel, TSMC, and Samsung Electronics – between 2019 and 2023. The main areas of research are greenhouse gas emissions, energy consumption, water usage, and waste management. This study identifies the varying environmental performance development of the examined companies and implemented mitigating measures. The findings highlight both areas of progress and persistent challenges within the sector. This underscores the need for greater transparency and standardization in sustainability reporting to facilitate the assessment of companies' environmental footprints and the effectiveness of implemented mitigation strategies.